SISTEM MONITORING POMPA PENDORONG AIR MENGGUNAKAN SENSOR TEKANAN BERBASIS INTERNET OF THINGS (IoT) - Joel Arya Tarigan (INOVTEK - Seri Elektro, 2025)
A water distribution system requires accurate pressure monitoring to ensure efficient pump operation. Conventional manual monitoring is prone to delayed fault detection, human error, and limited accessibility, which can lead to pipe damage, reduced efficiency, and system failure. This study proposes an Internet of Things (IoT)based monitoring system using a water pressure sensor and the PZEM-004T module to measure voltage, current, power, frequency, and power factor in real time. The system hardware includes a NodeMCU ESP8266 as the controller, a water pressure sensor, PZEM-004T V3, a 20x4 LCD, and a Bolt Slim Huawei E5372 WiFi modem. The software is developed using Arduino IDE to manage communication between components and integrate with the Android-based Blynk application. Testing was conducted under various faucet opening conditions to observe responses to pressure changes and pump electrical load. Results show data transmission to Blynk with an average delay of ±1.3 seconds. Voltage error was below 5%, current error reached 50% at low loads, and the highest power deviation was 14.8% when the faucet was partially open. Measured pressure ranged from 1.2 bar (closed) to 0.16 bar (fully open), with a power factor between 0.94 and 1.00. The system supports reliable remote monitoring and early warning of pressure anomalies.